PANDANGAN HUKUM ISLAM TERHADAP PENENTUAN DAN PEMBERIAN UANG PANAIK DALAM PERKAWINAN ADAT BUGIS DI DESA NUSANTARA JAYA KECAMATAN KERITANG KABUPATEN INHIL PROVINSI RIAU - Mustakim, Ahmad; Huda, Afiful; Mujahidin, M. (USRATUNA: Jurnal Hukum Keluarga Islam, 2022)
Panaik money is money given by the groom to the bride's familyas financing for the wedding ceremony, and one of the things that must begiven apart from the dowry. The determination of the panaik money inNusantara Jaya Village is carried out by deliberation between the groom'sfamily and the bride's family, and in terms of the amount of the gift it is seenfrom several aspects such as beauty, noble family, social strata, the higher thelevel of education the higher the amount of panaik money must be given. Thisarticle will discuss the Islamic view regarding determining and giving Panaikmoney in marriage. The type of research that the authors use is field research.While the approach used in this research is qualitative. The results of thisstudy indicate that giving Panaik money has become an ingrained habit amongthe Bugis community, especially in Nusantara Jaya Village. Some of the ways ofgiving are done in cash, some are done in installments according to theagreement of both parties. Meanwhile, for the determination of Panaik moneyby means of deliberation from both parties, the benchmark for Panaik moneycan be seen from education, beauty, respectable family, and others. There isnothing in the Qur'an and Hadith that discusses the existence of Panaik money,but Islamic law addresses this with the theory of the Al-'Adah Muhakkamahfiqh rules so that useful habits can continue to be carried out. If you look at theperpetrators, they are included in the category of 'urf hash, if you look at theirwork, they are 'urf fi'li.